THE PRESENCE OF POST-TRAUMATIC STRESS DISORDER (PTSD) LEVEL AT LOMBOK EARTHQUAKE SURVIVORS - Primalova Septiavy Estiadewi; Shrimarti Rukmini Devy; Hanik Endang Nihayati; Ah. Yusuf Ah. Yusuf (Alta Dharma Publisher, 2019)
Background Lombok earthquake was one of the major earthquakes that occurred in Indonesia. Earthquakes have caused many deaths and injuries also made survivors are at risk of suffering from trauma-related mental health disorders such as Posttraumatic Stress Disorder (PTSD). Objective This study aims to describe the incidence of trauma at 6 months after the Lombok earthquake. Methods This study is a descriptive study with a cross-sectional approach. There were 136 survivors of Lombok earthquake who were the subjects of the study. The technique of taking research survivor using purposive sampling technique. The instrument was using the Impact of Event Scale (IES). Data were analyzed descriptively using numbers and percentages. Results PTSD can occur in all men and women in adulthood. employment status, location of residence, and exposure to trauma recovery after 6 months of disaster are aspects that need to be considered in determining the incidence of PTSD. Conclusion After 6 months the Lombok earthquake was still found by survivors who had PTSD. Recommendation Survivors of earthquake natural disasters need psychological therapy to reduce the impact of post-disaster trauma